The preservative effect of Thai propolis extract on the viability of human periodontal ligament cells - Attaporn Prueksakorn (2018)
© 2016 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Background/Aim: Tooth avulsion causes an injury to the periodontal ligament (PDL). The success of tooth replantation depends on the quantity and quality of PDL cells. The aim of this study was to examine the preservative and proliferative effects of Thai propolis extract, previously shown to exert anti-inflammatory and antioxidant activities, on human PDL cells. Materials and methods: Ninety-six premolars were left to air dry for 30 min and stored in Hank's balanced salt solution (HBSS), milk, or various concentrations of propolis extract from 0.25 to 10 mg ml−1for 3 h. PDL cells were isolated by collagenase and trypsin digestion, and their viability was determined by a trypan blue dye exclusion assay. PDL tissues were also scraped off the root surface and cultured to determine cell growth and morphology. The alamarBlue®and BrdU assays were performed to determine the cytotoxic and proliferative effects of the extract on cultured PDL cells, respectively. Results: A non-toxic dose of 2.5 mg ml−1of propolis extract yielded the greatest percentage of cell viability (78.84 ± 3.34%), which was significantly higher than those of the other concentrations (P < 0.001). Nevertheless, this percentage was not significantly different from that of HBSS (80.14 ± 2.44%; P = 1.00), but was significantly higher than that of milk (71.27 ± 2.79%; P < 0.001). The cells grown from PDL explants looked like fibroblasts. However, 2.5 mg ml−1of the extract did not induce PDL cell proliferation. Conclusion: Thai propolis extract at 2.5 mg ml−1appears to be the most effective dose for preserving the viability of PDL cells, and this was comparable to HBSS.